The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/gcc.22511
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity of FISH analysis in detecting homozygous SMARCB1 deletions in poorly differentiated chordoma: a clinicopathologic and molecular study of nine cases

Abstract: Poorly differentiated chordomas (PDCs) represent a rare subset of notochordal neoplasms, affecting primarily children and associated with an aggressive outcome. In contrast to conventional chordomas, PDC show solid growth and increased cellularity, cytologic atypia, and mitotic activity. Recent studies have shown that PDCs are characterized by recurrent deletions encompassing the SMARCB1 locus, resulting in consistent loss of nuclear SMARCB1 expression. Thus PDC joined the expanding family of SMARCB1-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
(95 reference statements)
0
23
0
Order By: Relevance
“…6,8,10,12 This may be true even when there is morphologic over- SMARCB1 is a chromatin remodeling member of the SWI/SNF complex that has been known to be lost in a number of sarcomas, including malignant rhabdoid tumor, epithelioid sarcoma, epithelioid malignant peripheral nerve sheath tumor, and myoepithelial carcinoma. This finding correlates well with immunohistochemical loss of expression of SMARCB1, and prior FISH or MLPA analysis which shows homozygous SMARCB1 deletion in a majority of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,10,12 This may be true even when there is morphologic over- SMARCB1 is a chromatin remodeling member of the SWI/SNF complex that has been known to be lost in a number of sarcomas, including malignant rhabdoid tumor, epithelioid sarcoma, epithelioid malignant peripheral nerve sheath tumor, and myoepithelial carcinoma. This finding correlates well with immunohistochemical loss of expression of SMARCB1, and prior FISH or MLPA analysis which shows homozygous SMARCB1 deletion in a majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…This finding correlates well with immunohistochemical loss of expression of SMARCB1, and prior FISH or MLPA analysis which shows homozygous SMARCB1 deletion in a majority of cases. 6,8,10,12 This may be true even when there is morphologic over- expression by immunohistochemistry and SMARCB1 point mutations. 11 As a result, given the limited number of cases tested in this study, the possibility of other mechanisms of loss of SMARCB1 expression cannot be entirely excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Although they usually lack the physaliphorous cells (42/53, 79%) and an extracellular myxoid or chondroid matrix mimicking hyaline cartilage, tumors with INI1 loss and morphology resembling classical chordoma have been also reported . Cellular morphology and tissue pattern may vary as Owosho et al described in their cases as epithelioid, rhabdoid, spindled architecture in nests, acini, or solid form . Some cases were reported to show active to chronic inflammatory infiltrate (Fig.…”
Section: Histopathologymentioning
confidence: 99%
“…Homozygous or heterozygous SMARCB1 deletions which can be shown by fluorescent in situ hybridization (FISH) or multiplex ligation‐dependent probe amplification (MLPA) seem to be the main mechanism. Owosho et al performed fluorescence in situ hybridization (FISH) directed at chromosome 22q11–12 region, which showed that all cases demonstrated homozygous SMARCB1 deletions except one. They also claimed that FISH is more sensitive than MLPA in the detection of INI1 losses.…”
Section: Molecular Studiesmentioning
confidence: 99%
See 1 more Smart Citation